Research knowledge and needs for orchard floor management in organic tree fruit systems - Granatstein, David; Sanchez, Enrique Eduardo (Taylor and Francis, 2024)
While pest management and tree horticulture dominate the research agenda for temperate tree fruits, organic production requires more attention to weed control and nutrient management because of the limited options growers have. Weed control and tree nutrition are interlinked and can have impacts on other parts of the system such as rodent pests, beneficial insect habitat, water use, and soil quality. Trade-offs commonly occur when trying to solve weed control and nutrient management in organic orchards. This article reviews numerous orchard-floor management studies relevant to finding solutions for organic systems and suggests areas for further research. Alternatives to soil tillage are needed, as it can degrade soil and tree performance. Conversely, mulching frequently leads to improved tree performance and increased soil quality but can be a costly practice relative to other options. Currently effective organic analogues to the herbicide strip-grass alley system are lacking. A plant-based solution would be ideal from a sustainability standpoint, but no satisfactory solution has been developed for widespread use.